Study on Calf Morbidity and Mortality on Farm Condition with Special Emphasis on Colibacillosis - Singh, A. K.; Islam, Md. R.; Adhikari, R. K. (Nepalese Veterinary Journal, 2019)
Diarrhoea in farm animals, especially in neonatal calves is one of the most challenging clinical syndromes encountered by practicing large animal’s veterinary practitioners throughout the world. Therefore looking into the complexity of early age calf diarrhea primarily due to E. coli, the present study was conducted in different dairy farm in Sylhet Sadar in order to determine the major cause and risk factor associated with calf morbidity and mortality due to colibacillosis. The main result revealed that out of 121 calves different ages were selected where calf manifesting the characteristics clinical sign of colibacillosis. From thirteen dairy farms in Sylhet sadar out of 121 samples 75 were observed affected with colibacillosis. The overall morbidity of calf colibacillosis was 61.98% and mortality were 00.00%. Data analysis showed that the calf colibacillosis in dairy farms due to many factors such as age was the only risk factor (calf factor) which was highly significantly (χ2 = 13.003, P-value = 0.000) washing of udder just before sucking milk to calf was statistically highly significant (χ2 = 7.373, P-value = 0.007) which means washing of udder just before sucking milk to calf lowers the calf morbidity due to colibacillosis. Milk replacer sanitation was statistically significant (χ2 = 6.5, P-value = 0.011) water supply to the calf was statistically significant (χ2 = 4.247, P-value = 0.039) which means hygienic water supply to calf lowers the calf morbidity due to colibacillosis. Proper drainage system (χ2 = 4.069, P-value = 0.044) and daily use of disinfectant in farm premises (χ2 = 6.163, P-value = 0.013). The mortality of calf due to colibacillosis was null because of proper treatment, knowledge of management of diseased calf and availability of veterinarians. Morbidity and mortality of calf colibacillosis in different dairy farm at Sylhet sadarUpazila were 61.98% and 0.00% respectively.